Analysis of the Language Style of Vanity Fair - Chen, Ying; Zhang, Yingjia; Wang, Linghui; He, Zhaoying (Journal of Theory and Practice of Contemporary Education, 2023)
Vanity Fair is one of the famous literary works in England, with a high status. The content of the novel mainly depicts two completely different female protagonists, presenting the life of capitalist society in England to readers at that time. This article first analyzes the thematic ideas expressed in the novel, focusing on the language style characteristics of the novel from the perspectives of satirical language and unique narrative methods, for reference only. The most important aspect of an excellent literary work is the language style, which can reflect the author's style characteristics, and the language can reflect the various contents of the novel. In the work "Vanity Fair", the author actually criticizes the corruption and bad atmosphere of the society at that time. However, the author did not directly criticize it, but instead presented the theme and ideas of the novel to the readers through humorous language. Therefore, this article hopes to explore the language style of "Vanity Fair" and understand the language characteristics of 19th century British literary works. With the vigorous development of internet technology and the continuous deepening of digitization, the world has entered the digital era. Currently, the digital economy accounts for nearly 40% of China's total economy.